Covenant Strictness Measures - Ding, Jianglin Dennis; Witt, Alan (Journal of Accounting and Finance, 2024)
Covenants are crucial components of loan agreements, designed to protect lenders by imposing various restrictions and obligations on borrowers. Despite extensive empirical research on covenant strictness, a universally accepted measure of covenant strictness remains elusive. Existing metrics tend to include only a limited selection of covenants from the comprehensive contract. This study utilizes loan-level credit risk data to evaluate and rank the effectiveness of several widely used covenant strictness measures. Credit risk at the loan level is assessed through two primary methods: the difference between issue ratings and issuer ratings, and the loan credit spread while controlling for fixed effects at the firm level. This approach allows for a more nuanced comparison and provides insights into which measures most accurately reflect covenant strictness and its impact on credit risk. The findings aim to contribute to a better understanding of covenant effectiveness, offering potential improvements for future loan contract structuring and risk assessment practices.